Perspektif Ekonomi Islam terhadap Sistem Mato dalam Pembagian Keuntungan Rumah Makan Padang - Sasra Dafit Akbar; Rizal Fahlefi; Miftahul Jannah; Ahmad Lutfi (Lembaga Pengembangan Kinerja Dosen, 2026)
The mato system is a traditional profit-sharing model that has long been practiced in the management of Padang restaurants. This system reflects the values of justice, honesty, and collective cooperation, all of which are aligned with the principles of Islamic economics. However, in modern business settings, the mato system has gradually shifted toward a fixed-wage arrangement ijarah driven by managerial efficiency demands and business modernization. This study aims to examine the mato system from an Islamic economic perspective by highlighting its value transformation and relevance within contemporary business contexts. The research employs a Systematic Literature Review SLR combined with field-based case illustration from Padang restaurants in West Sumatra, particularly Rumah Makan Lamun Ombak. Data were obtained from scientific publications 2015–2025, official BPS reports, and supporting interview data. Thematic analysis was conducted to interpret core Sharia values such as ‘adl justice, ṣidq honesty, ta‘āwun cooperation, and shafāfiyyah transparency. The findings reveal that the shift away from the traditional mato system does not eliminate Islamic values; rather, it encourages the emergence of an adaptive model referred to as the Hybrid Islamic Profit-Sharing System HIPSS, which combines elements of musyarakah and ijarah. This model maintains a balance between economic certainty and distributive justice. The study concludes that revitalizing the foundational values of the mato system has the potential to enrich locally rooted Islamic economic practices in Indonesia.